Risk Reduction of Adverse Effects Due to Di-(2-Ethylhexyl) Phthalate (DEHP) by Utilizing Microbial Degradation - Baek, Ji Hye; Gu, Man Bock; Sang, Byoung-In; Kwack, Seung Jun; Kim, Kyu Bong; Lee, Byung Mu (TAYLOR & FRANCIS INC, 2009)
Di-(2-ethylhexyl) phthalate (DEHP), one of the major phthalates, was reported to be a suspected endocrine-disrupting chemical (EDC) that might produce developmental or reproductive toxicities. Therefore, much effort was undertaken to reduce the potential risk of adverse effects of DEHP on humans by diminishing environmental exposure to this chemical. A bacterium was isolated from soil contaminated with DEHP at a poly(vinyl chloride) (PVC) manufacturing site. Biodegradation kinetic experiments on DEHP-contaminated soil samples were performed in a slurry phase system. The DEHP concentration was decreased to a concentration of 0.5 g/kg by the addition of 1% culture medium to the soil. The microorganism degraded DEHP through the formation of a mono-2-ethylhexyl phthalate (MEHP), which was subsequently metabolized to phthalic acid (PA), as detected by GC-MS analysis. Micrococcus luteus was able to degrade almost 90% of the initial DEHP within 12 d. In addition, the microbial toxicity study of DEHP and its degradation products MEHP or PA, using recombinant bioluminescent bacteria, showed that PA or the mixture produced protein or DNA damage. Data thus suggest that a new strain of Micrococcus luteus with a strong ability to degrade DEHP into nontoxic metabolites may contribute to decontamination of environmental phthalates and consequently risk reduction of human exposure to DEHP.
Keywords: BUTYL BENZYL PHTHALATE; ENDOCRINE-DISRUPTING CHEMICALS; ESCHERICHIA-COLI STRAIN; DI(2-ETHYLHEXYL)PHTHALATE DEHP; DI-2-ETHYLHEXYL PHTHALATE; MANGROVE SEDIMENT; OXIDATIVE STRESS; ACID-ESTERS; IN-VITRO; PLASTICIZERS